Pendekatan Ergonomi Partisipatif untuk Pencegahan Gangguan Muskuloskeletal pada Pekerja Sektor Informal - Cita Fitria Putri; Ekawati Ekawati (Universitas Faletehan, 2025)
Musculoskeletal disorders are a significant global health concern, particularly impacting informal workers who lack organized occupational health services. Participatory ergonomic approaches present a solution by engaging workers in recognizing hazards and improving their work settings. This scoping review outlines evidence on participatory ergonomic interventions for preventing MSDs in informal work environments. A search was performed across PubMed, Scopus, ProQuest, EBSCO, ScienceDirect, and Google Scholar for studies published up to 2025. Studies qualified if they focused on informal workers, used participatory ergonomic approaches, and documented MSD prevention outcomes. Ten studies were selected for analysis. Interventions primarily focused on modifying tools, workstations, and facilities based on workers' body measurements and job requirements. Other approaches included ergonomic aids, stretching programs, and workplace layout reorganization. Workers participated through interviews, focus groups, observations, and risk assessments. Results showed reduced musculoskeletal complaints by up to 47.9%, improved posture, reduced workload, and increased productivity. Implementation barriers included limited finances, traditional work practices, lack of ergonomic awareness, and resistance to change. These findings highlight the need to customize interventions for specific socio-economic and cultural contexts. Participatory ergonomics can improve informal workers' health, but future studies should examine methods for ensuring long-term viability and cultural adaptation of these interventions.